2007
DOI: 10.1021/ef060346g
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Combustion Characteristics and Flame Length of Turbulent Oxy−Fuel Flames

Abstract: Combustion characteristics, flame structure, and length in an oxy-fuel combustor have been experimentally investigated for a wide range of fuel nozzle diameters and fuel and oxidizer velocities. Measurements are made for the model combustor (Combustor I) as well as for the actual oxy-fuel combustor (Combustor II). The experimental results for Combustor I clearly reveal basic features of the air-fuel and oxy-fuel flames in terms of flame length and structure. It was found that the flame length of the oxy-fuel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 15 publications
(18 reference statements)
3
22
0
1
Order By: Relevance
“…4). The oxy-fuel flame has been reported to show a higher intensity than the air-fuel flame [7], and indeed the flame images produced in the present study show that trend distinctively under the high combustion loads of 24 kW and 29 kW. Under a higher combustion load, the flame cohered just downstream of the burner, in the cases of oxy-fuel, and showed a faster flame propagation than that for the cases of air combustion.…”
Section: Flame and Temperature Fieldssupporting
confidence: 69%
“…4). The oxy-fuel flame has been reported to show a higher intensity than the air-fuel flame [7], and indeed the flame images produced in the present study show that trend distinctively under the high combustion loads of 24 kW and 29 kW. Under a higher combustion load, the flame cohered just downstream of the burner, in the cases of oxy-fuel, and showed a faster flame propagation than that for the cases of air combustion.…”
Section: Flame and Temperature Fieldssupporting
confidence: 69%
“…They derived a simple correlation of the flame length and volume relative to the flow parameters for the high-temperature air combustion condition. Kim et al [22] proposed a modified correlation between dimensionless flame lengths and a flame Froude number to estimate L f for the two kinds of oxy-fuel combustors. Hu et al [23] measured flame length at a reduced atmospheric pressure for turbulent buoyant jet diffusion flames; it was reported that the normalized L f was longer in the lower pressure atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the organization of combustion with exothermic oxidation of fuel takes place. The gaseous products of incomplete combustion go through a window in the upper end wall [11,12]. The disadvantage of the method is a high degree of underburning of the gaseous bulk residue introduced, the inability to use it in the production of silicate products (bricks, tiles, blocks), as well as the low heat content and heat of combustion of the gaseous combustion products withdrawn from the furnace, and the inability to use them effectively.…”
Section: Introductionmentioning
confidence: 99%